Content Analysis of the Book of "Arabic Is My Language " , third level , B curriculum in Syrian Arab Republic concerning Listening and Speaking Skill available in it (Journal of Hama University, 2022)
Content Analysis of the Book of "Arabic Is My Language " , third level , B curriculum in Syrian Arab Republic concerning Listening and Speaking Skill available in it . Al-Fella (B) The book's deception according to the standard built by the researcher , knowledge, the degree of its availability in the book, to achieve these goals, and then follow the descriptive analytical approach, using the research tool, which is a standard for analyzing the book, which strengthened listening and speaking skills. The research reached the following results: the lack of mastery of listening skills in the book, as they were not mentioned in the book, whether through exercises included in other lessons, and the achievement of most of the speaking skills; Where they were not mentioned in the book intentionally through exercises included in other lessons or through individuals special lessons for speaking skill, and the rest of the speaking skills.